Matrix Stiffness Affects Glycocalyx Expression in Cultured Endothelial Cells - Mahmoud, Marwa; Cancel, Limary; Tarbell, John M. (Frontiers in Cell and Developmental Biology, 2021)
Rationale: The endothelial cell glycocalyx (GCX) is a mechanosensor that plays a key role in protecting against vascular diseases. We have previously shown that age/disease mediated matrix stiffness inhibits the glycocalyx glycosaminoglycan heparan sulfate and its core protein Glypican 1 in human umbilical vein endothelial cells, rat fat pad endothelial cells and in a mouse model of age-mediated stiffness. Glypican 1 inhibition resulted in enhanced endothelial cell dysfunction. Endothelial cell culture typically occurs on stiff matrices such as plastic or glass. For the study of the endothelial GCX specifically it is important to culture cells on soft matrices to preserve GCX expression. To test the generality of this statement, we hypothesized that stiff matrices inhibit GCX expression and consequently endothelial cell function in additional cell types: bovine aortic endothelial cells, mouse aortic endothelial cell and mouse brain endothelial cells. Methods and Results: All cell types cultured on glass showed reduced GCX heparan sulfate expression compared to cells cultured on either soft polyacrylamide (PA) gels of a substrate stiffness of 2.5 kPa (mimicking the stiffness of young, healthy arteries) or on either stiff gels 10 kPa (mimicking the stiffness of old, diseased arteries). Specific cell types showed reduced expression of GCX protein Glypican 1 (4 of 5 cell types) and hyaluronic acid (2 of 5 cell types) on glass vs soft gels. Conclusion: Matrix stiffness affects GCX expression in endothelial cells. Therefore, the study of the endothelial glycocalyx on stiff matrices (glass/plastic) is not recommended for specific cell types.